The relationship between maxillary and mandibular lengths of ethnic Bataks of chronological age 9–15 years - Hilda Fitria Lubis; Nurul Ulfa Simanjuntak (Dental Journal (Majalah Kedokteran Gigi), 2022)
Background: Maxillary and mandibular growth have an important role in determining diagnosis and treatment plans. Knowledge of the growth of the maxilla and mandible becomes very important in designing a proper treatment plan and knowing the mean maxillary and mandibular lengths from the ages of 9–15 means malocclusion can be treated at the appropriate age. Purpose: The aim of this study was to determine the relationship between 9–15-year-old males and females and the length of the maxilla and mandible. Methods: This study used a cross-sectional design. The subjects consisted of 35 male and 45 females aged 9–15 years and 80 cephalometric radiograms were collected using a purposive sampling method from Universitas Sumatera Utara (USU) Oral and Dental Hospital based on inclusion and exclusion criteria. Data were collected by tracing the lateral cephalogram, the maxillary length and mandible lengths being measured on the cephalogram based on the McNamara method through a computer program, CorelDRAW. Pearson’s correlation coefficient was used for statistical analysis. Results: The average maxillary length for 9–15-year-olds was 96.35 ± 7.56 mm. The mean mandibular length for 9–15-year-olds was 122.29 ± 10.43 mm. Based on assessment and result, using the Pearson correlation coefficient test between maxillary length and mandibular length and chronological age, a maxillary length of p=0.003 and mandibular length of p=0.00 were obtained. Conclusion: There was a significant positive relationship between chronological age and maxillary length and mandibular length in 9–15-year-olds of Batak ethnicity.